(untitled) (Journal of Science and Technology, 2016)
In Ghana and most African countries, prostate cancer is the most common cancer in males after hepatocellular carcinoma. Whereas in the advanced countries, screening for prostate specific antigen (PSA) has led to early detection and management of the disease, screening has been very low in Ghana, thus leading to low detection rate, poor management and increased mortality. The aim of our study therefore was to provide the basis for the advocacy and promotion of prostate cancer screening in Ghana so as to improve early detection, management and prognosis. To do this, we estimated serum PSA levels of 196 men randomly reporting to the Out-Patient Department (OPD) of the Komfo Anokye Teaching Hospital for screening. We employed the enzyme immunoassay (EIA) method as our non-invasive screening procedure. We also conducted a survey on the prevalence of the disease as reported at five major hospitals in the country. It was observed that 83.6% of the subjects had their PSA levels above the upper limit of the reference range (4 ng/ml), with their ages ranging between 56 to 85 years. Coincidentally, our survey also revealed that 96.5% of those who had the disease within the period of study were above 50 years. The significance and relevance of these findings to PSA screening in the country and its accuracy in diagnosing prostate cancer cannot be overemphasized.